Information Security Controls as Determinant of Continuity of Information System Work - Edin Osmanbegovic; Nedzad Piric; Mirza Suljic (Economic Review: Journal of Economics and Business, 2017)
The purpose of this research is to identify the influence of information security controls on the continuity of information system work. The fact that the companies operate in highly turbulent business environment with severe threats to information security, leads to the need to examine this issue in detail. In their research, the authors have presented the indicators of impact of information security controls on the continuity of information system work. From the point of information security policy prescription, out of the total number of the surveyed companies, 80% do not have the required policy or a document showing the management commitment (attitude) to the introduction of information security measures. About 84% of the surveyed companies have information system access control. About 32% of these companies have the controls at the level of computer network, 22% of them have the control at the operating system level, while 38% have the control at the software application level. From the aspect of information system physical security, the surveyed companies (84%) indicated that they devote a considerable attention to this segment of information security. When analysing the existence of prescribed procedures for information system incident management, the study determined that only 20% of the companies have implemented these procedures. The prescribed procedures for monitoring information system continuity in the surveyed companies are at a very low level, as most of the companies (84%) do not have a proper procedure.
Keywords: 330; Information security; Aspects and procedures of information security; Information system continuity; Protection of companies' information resources